Complex Systems and Self-organization Modelling - Bertelle, Cyrille.; Duchamp, Gřard H.E.; Kadri-Dahmani, Hakima. (Understanding Complex Systems,, 2009)
The concern of this book is the use of emergent computing and self-organization modelling within various applications of complex systems. The authors focus their attention both on the innovative concepts and implementations in order to model self-organizations, but also on the relevant applicative domains in which they can be used efficiently. This book is the outcome of a workshop meeting within ESM 2006 (Eurosis), held in Toulouse, France in October 2006.